2022
DOI: 10.1039/d2nr02501a
|View full text |Cite
|
Sign up to set email alerts
|

Laminar flow-assisted synthesis of amorphous ZIF-8-based nano-motor with enhanced transmigration for photothermal cancer therapy

Abstract: Enzyme-powered nano-motors have promising applications in various fields owing to their biocompatibility. However, enzymes can undergo denaturation by harsh conditions. Here, we report a flow-assisted synthesis of enzyme-based amorphous ZIF-8...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…These components are currently being explored for their potential applications in targeted drug delivery and bio-precise sensing. [93,94] Drug-carrying micro-nanomotors can achieve excellent tumor penetration performance under their autonomous motion, thereby enhancing the therapeutic effects of drugs. Previously, the development of nanomotors has been hindered by limitations in the penetration depth of the nanoparticlemodified motor bases, which are primarily based on NIR-I light absorption.…”
Section: Dopamine-based Hydrogelmentioning
confidence: 99%
“…These components are currently being explored for their potential applications in targeted drug delivery and bio-precise sensing. [93,94] Drug-carrying micro-nanomotors can achieve excellent tumor penetration performance under their autonomous motion, thereby enhancing the therapeutic effects of drugs. Previously, the development of nanomotors has been hindered by limitations in the penetration depth of the nanoparticlemodified motor bases, which are primarily based on NIR-I light absorption.…”
Section: Dopamine-based Hydrogelmentioning
confidence: 99%
“…The Pdop core flow acted as a synthetic barrier, with the mass of reagents from the sheath flow being able to control the amount of transfer and the mass transfer of reagents in the sheath flow, effectively coiling the enzyme into a self-assembled, amorphous ZIF-8 shell, with quenching of core–shell products, and membrane filters were necessary to remove unreacted reagents in a timely manner. 57 Zhao et al first synthesised DNAzyme-loaded nanoparticles to mimic viral nucleocoats containing genomes. Zn 2+ -dependent DNAzyme (named TD) was encapsulated into ZIF-90 nanoparticles (named Z@TD) using a one-step synthesis procedure.…”
Section: Chemical Synthesis and Preparation Of Zn-mofsmentioning
confidence: 99%
“…The nanomotor offered high transmigration which had a powerful effect on BC cell ablation via PTT. [ 172 ] Realizing the intelligent controlled release of nanocarriers is also an index to test MOF materials as better drug carriers. These studies have shown that MOFs present advantages in enhancing drug therapy, whether in drug loading or in the dynamic therapy of nanomaterials.…”
Section: Nanomaterials For Bc Therapymentioning
confidence: 99%